Dermoid Cyst in the Suprasternal Space as a Rare Location - Yentürk, Eylem; Saygın, Tüzel (Cerrahpaşa Medical Journal, 2024)
Cite this article as: Yentürk E, Saygın T. Dermoid cyst in the suprasternal space as a rare location. Cerrahpaşa Med J. 2024;48(2):199-200.